Thickness dependence of Pb(Zr0.52Ti0.48)O-3 films prepared by pulsed laser deposition - Kim, MC; Choi, JW; Yoon, SJ; Yoon, KH; Kim, HJ (JAPAN SOC APPLIED PHYSICS, 2002)
The films of nominal composition Pb(Zr0.52Ti0.48)O-3 (PZT) in the thickness range of 0.4-6.0 mum were fabricated on Pt/Ti/SiO2/Si substrate using a pulsed laser deposition (PLD). The PZT films were deposited in a single process at 500degreesC and post annealed at 650degreesC in oxygen atmosphere. The variations in preferred orientation and microstructure were determined as a function of film thickness. The transition of preferred orientation and microstructure influenced dielectric property. Ferroelectric and dielectric properties were maximized at the film thickness of 2.0 mum. The maximum values of remnant polarization and dielectric constant were 38 mummuC/cm(2) and 1380, respectively.
Keywords: TITANATE THIN-FILMS; LEAD-ZIRCONATE; STABILITY; ABLATION; QUALITY